Effect of Preservation Time, Light and Temperature of Cyanobacterial Extract, Phormidium angustissimum, on the Inhibit Seed Germination Ability of Chinese Cabbage - เรืองสมบูรณ์ สุนีรัตน์; ชูโชติ ศักดิ์ชัย; เอื้ออำนวย ดุสิต (KKU Science Journal, 2013)
The effect of preservation time, light and temperature on stability of cyanobacterium; Phormidium angustissimum extract to inhibit the germination of bioassay seed, Brassica chinensis var. parachinensis Tsen & Lee, were studied. Cyanobacterial extracted by water and methanol were kept under different conditions; 4oC and 25oC with and without light for 0 to 15 days. The stability of cyanobacterial extracts to inhibit the germination of bioassay seed were tested at 0, 1, 2, 3, 5, 7, 9, 11, 13 and 15 days. At 0-11 days of preservation in all conditions, cyanobacterial extracted by methanol showed 100% inhibit the germination of bioassay seed. The inhibition efficiency was decreased when the preservation time increased. Cyanobacterial extracts preserve at 4oC had more inhibitory effect on the germination than at 25oC. Keeping the cyanobacterial extracts in the dark showed higher inhibitory effect on germination compared to that under the light.